(untitled) (Journal of Comparative Social Work, 2014)
This article focuses on how families are defined and conceptualized by social workers in the Swedish social services. Using a qualitative study design, we carried out telephone interviews with 60 social workers in five major sectors of the social services in two smaller and two larger municipalities. These sectors included elderly care, disability, child welfare, addiction and economic support, with a qualitative content analysis approach used to analyze the data.The results showed that the practices in social service organizations are both individualized and specialized. Social workers primarily focus on the individual as the client when deciding upon interventions, and when asked about how they regard, define and delimit the family in their work, our analysis revealed that different mediating mechanisms were engaged in what can be seen as a deconstruction of the family. These mechanisms included legislation (as a control mechanism), household composition (boundary mechanism) and service needs (professional mechanism), which were used in various ways and to differing degrees within each sector. The resultant five unique and sector-specific conceptualizations of families are implicated in how interventions are constructed and work processes targeted at individuals and families.